2020
DOI: 10.21608/ejap.2020.92778
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Using Olive Cake Meal With or Without Sodium Bicarbonate on Productive Performance of Growing New Zealand White Rabbits

Abstract: The present experiment was carried out to investigate the possibility of incorporating 10 and 20 % of olive cake meal (OCM) with or without 0.25% and 0.50% sodium bicarbonate (NaHCO 3 ) in the rabbit diets and their effects on growth performance, carcass traits, blood constituents, nutrient utilization and economical efficiency of growing rabbits. A total of 105 unsexed, New Zealand White (NZW) weaned rabbits of 4 weeks of age were randomly assigned to 7 equal experimental groups (15 rabbits each). Rabbits wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
(26 reference statements)
1
0
2
Order By: Relevance
“…Results obtained of LBW and BWG in the present study disagree with these reported by Azazi et al (2020) who found that the rabbits fed on the diet supplemented with 10 % olive cake meal with 0.25 sodium bicarbonate (NaHCO3) recorded the highest value of final body weight, total gain and daily weight gain. Also, Balnave and Oliva (1991) noted that supplemented with NaHCO3 in diets or drinking water produced a significant improvement in birds.…”
Section: Growth Performance Live Body Weight and Body Weight Gaincontrasting
confidence: 99%
See 2 more Smart Citations
“…Results obtained of LBW and BWG in the present study disagree with these reported by Azazi et al (2020) who found that the rabbits fed on the diet supplemented with 10 % olive cake meal with 0.25 sodium bicarbonate (NaHCO3) recorded the highest value of final body weight, total gain and daily weight gain. Also, Balnave and Oliva (1991) noted that supplemented with NaHCO3 in diets or drinking water produced a significant improvement in birds.…”
Section: Growth Performance Live Body Weight and Body Weight Gaincontrasting
confidence: 99%
“…There were not significant differences among the experimental treatments for the intestinal weight and length (%).The value of cecum weight was observed with T1 compared to the control and other treatments, control group. The results of Azazi et al (2020) disagree with our results where the rabbits fed 10 % olive cake meal plus 0.25 or 0.50% sodium bicarbonate (NaHCO3) had the highest significance (P≤0.01) value of carcass (%) compared with the others. On the other hand, rabbits fed on the diet supplemented with 10% olive cake meal without NaHCO3 had the lowest values of all traits.…”
Section: Carcass Traitscontrasting
confidence: 99%
See 1 more Smart Citation
“…These trials have demonstrated the viability of incorporating olive cake into fattening diets without compromising growth performance. The consensus suggests that such inclusion improves the economic efficiency of rabbit production, given that feed constitutes a substantial proportion of overall costs (Kadi et al, 2004;Chaabane et al, 1997;Dorbane et al, 2016;Salama et al, 2016;Bakr et al, 2019;Dorbane et al, 2019;Rupić et al, 2019;Wahed et al, 2019;Azazi et al, 2020). Conversely, the use of EOC in rabbit production remains relatively unexplored.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%